Monitoring and locating missing persons using Arduino and GSM/GPS - Padilla, Roberto (2016)
The objective of this work is to develop a device capable of monitoring a person is in danger or loss, plus a half alert to notify if the person requires immediate help. The components used in this Project are very low cost, making it more attractive compared to other satellite monitoring devices. Another advantage of this project is the flexibility of use, as it can be adapted to different areas, from security to health monitoring, and thanks to the freedom offered by the Arduino platform, it is possible to exploit the full potential of all data obtained. In this study we show the initial progress in this device, and future challenges.